Case of adult-onset Kawasaki disease and multisystem inflammatory syndrome following SARS-CoV-2 vaccination. Issue 7 (4th July 2022) - Showers, Christopher R; Maurer, Jaslyn M; Khakshour, Doreen; Shukla, Mohit
Abstract : Kawasaki disease (KD) and multisystem inflammatory syndrome (MIS) are rare conditions that occur predominately in children. Recent reports document KD and MIS in adult patients following infection with SARS-CoV-2. Rarely, MIS is observed following vaccination against SARS-CoV-2, mostly in patients with prior SARS-CoV-2 infection. We report a case of KD in a man after a second SARS-CoV-2 vaccine dose, in absence of concurrent or prior SARS-CoV-2 infection. This patient also met criteria for probable MIS associated with vaccination. He tested negative for SARS-CoV-2 RNA via reverse transcriptase PCR, negative for SARS-CoV-2 nucleocapsid antibodies and demonstrated high levels SARS-CoV-2 spike protein antibodies, commonly used to assess vaccine response. Symptom improvement followed treatment with intravenous immunoglobulin, including desquamation of the hands and feet. As widespread vaccination against SARS-CoV-2 continues, increased vigilance and prompt intervention is necessary to limit the effects of postvaccination inflammatory syndromes.